UTILIZING QAWĀ’ID FIQHIYYAH IN LEGAL ANALYSIS: A REVIEW OF THEIR EVOLUTION AND APPLICATION IN INDONESIAN ISLAMIC JURISPRUDENCE - Jalili, Ismail; Syukri, Ilham (istinbath, 2025)
The study of Qawā’id Fiqhiyyah or Islamic legal maxims, plays a crucial role in contemporary legal analysis and application within Indonesian Islamic jurisprudence. This research explores the brief historical evolution and modern utilization of these legal maxims, emphasizing their significance in shaping legal outcomes in Indonesia's dynamic socio-religious landscape. The study aims to shed light on how Qawā’id Fiqhiyyah has been adapted and integrated into the Indonesian legal system, providing a framework for resolving complex legal issues in a manner consistent with Islamic principles. This research examines the evolution of Qawā’id Fiqhiyyah (Islamic legal maxims), exploring their foundational roots in classical Islamic jurisprudence and analyzing their adaptation and relevance in contemporary Indonesian legal and societal contexts. It highlights how these maxims have provided a bridge between traditional Islamic law and the modern legal challenges faced by a diverse Muslim population. The research method employed includes a qualitative analysis of legal texts and case studies, offering a comprehensive overview of the practical application of these maxims. The results reveal that Qawā’id Fiqhiyyah has been instrumental in providing clarity and consistency in legal reasoning, contributing to a more coherent and adaptable legal system. The research identifies specific maxims frequently applied in Indonesian jurisprudence and analyzes their impact on legal decisions and policymaking. In conclusion, the study underscores the importance of Qawā’id Fiqhiyyah as a vital tool in the Indonesian legal context, advocating for their continued evolution and adaptation to meet the needs of an ever-changing society.